2016
DOI: 10.1002/cphc.201600683
|View full text |Cite
|
Sign up to set email alerts
|

On the Versatility of BH2X (X=F, Cl, Br, and I) Compounds as Halogen‐, Hydrogen‐, and Triel‐Bond Donors: An Ab Initio Study

Abstract: In this manuscript, the ability of BH X compounds (X=F, Cl, Br, and I) to establish halogen-, hydrogen-, and triel-bonding interactions was studied at the RI-MP2/aug-cc-pVQZ level of theory. Several homodimers were taken into account, highlighting the versatility of these compounds to act as both electron donors and electron acceptors. Natural bond orbital analysis showed that orbital effects were important contributors to the global stabilization of the σ- and π-hole bonded complexes studied. Finally, some X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…A study into the charge distribution in haloboranes (BH 2 X, X = F, Cl, Br, I) has revealed different types of σ-hole and π-hole non-covalent interactions in the solid-state that exhibit different bonding strengths and geometries. 49 The directional charge distribution on the halogen atoms in [B 12 X 12 ] 2-anions may lead to strong directional bonds to Na + and increase the resistance to reorientational anion disorder in the structure, forcing the polymorphic phase transition to high temperature. In fact, sodium is bound in a deep electrostatic potential well, in-between two halide atoms on the [B 12 2-anion.…”
Section: Discussionmentioning
confidence: 99%
“…A study into the charge distribution in haloboranes (BH 2 X, X = F, Cl, Br, I) has revealed different types of σ-hole and π-hole non-covalent interactions in the solid-state that exhibit different bonding strengths and geometries. 49 The directional charge distribution on the halogen atoms in [B 12 X 12 ] 2-anions may lead to strong directional bonds to Na + and increase the resistance to reorientational anion disorder in the structure, forcing the polymorphic phase transition to high temperature. In fact, sodium is bound in a deep electrostatic potential well, in-between two halide atoms on the [B 12 2-anion.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its important roles in numerous chemical processes, more attention has been paid to triel bonding . Besides the lone‐pair electrons, π‐electrons in aromatic or unsaturated molecules and the single electron in radicals are also taken as Lewis bases in triel bonding.…”
Section: Introductionmentioning
confidence: 99%
“…When BX 3 (X = F, Cl, Br and I) compounds bind with π‐systems including ethene, 1,2‐difluoroethene and perfluoroethene, lone pair–π, halogen and triel bonding interactions are established, but triel bonding is the most favorable among the three types of interactions . Similarly, BH 2 X (X = F, Cl, Br and I) can participate in hydrogen, halogen and triel bonds in its homodimeric systems owing to its dual σ‐ and π‐hole nature . Charge‐assisted triel bonding interactions have also been evidenced in solid‐state chemistry .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations